VOTES AND SEATS. PROPORTIONAL REPRESENTATION IN TIERRA DEL FUEGO // VOTOS Y BANCAS. LA REPRESENTACIÓN PROPORCIONAL EN TIERRA DEL FUEGO (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The Provincial Supreme Law established a regulatory scheme that was not limited to the mere enunciation of principles to be observed by the electoral regime to be sanctioned. It expressly provided that the electoral law regulating the election of collegiate body members should guarantee “effectively proportional representation”. The constitutional provision was regulated by the Provincial Act No. 201, which established the process of renewal of elective authorities and adopted the proportional D'Hondt formula to determine the composition of the Legislative Branch. A brief analysis of electoral processes that took place between 1991 and 2015 will show how close to constitutional ambitions were the results produced by the electoral system.
Keywords: electoral law; Tierra del Fuego; proportional represntation